Zinc2+ ion inhibits SARS-CoV-2 main protease and viral replication in vitro. Issue 78 (13th September 2021) - Panchariya, Love; Khan, Wajahat Ali; Kuila, Shobhan; Sonkar, Kirtishila; Sahoo, Sibasis; Ghoshal, Archita; Kumar, Ankit; Verma, Dileep Kumar; Hasan, Abdul; Khan, Mohd Azeem; Jain, Niyati; Mohapatra, Amit Kumar; et al.
Abstract : Zn 2+ binds to the active site of the SARS-CoV-2 main protease (Mpro), and inhibits enzyme activity and viral replication in vitro . Abstract : Zinc deficiency is linked to poor prognosis in COVID-19 patients while clinical trials with zinc demonstrate better clinical outcomes. The molecular targets and mechanistic details of the anti-coronaviral activity of zinc remain obscure. We show that zinc not only inhibits the SARS-CoV-2 main protease (Mpro) with nanomolar affinity, but also viral replication. We present the first crystal structure of the Mpro–Zn 2+ complex at 1.9 Å and provide the structural basis of viral replication inhibition. We show that Zn 2+ coordinates with the catalytic dyad at the enzyme active site along with two previously unknown water molecules in a tetrahedral geometry to form a stable inhibited Mpro–Zn 2+ complex. Further, the natural ionophore quercetin increases the anti-viral potency of Zn 2+ . As the catalytic dyad is highly conserved across SARS-CoV, MERS-CoV and all variants of SARS-CoV-2, Zn 2+ mediated inhibition of Mpro may have wider implications.